The modulation of potassium channels by estrogens facilitates neuroprotection - Li, Xian-Tao (Frontiers in Cell and Developmental Biology, 2022)
Estrogens, the sex hormones, have the potential to govern multiple cellular functions, such as proliferation, apoptosis, differentiation and homeostasis, and exert numerous beneficial influences for cardiovascular system, nervous system and bone through genomic and/or non-genomic ways. Converging evidence indicates that estrogens serve a crucial role in counteracting neurodegeneration and ischemic injury, thereby being considered as a potent neuroprotectant for preventing neurological diseases such as Alzheimer’s disease (AD) and stroke. The underlying mechanism of neuroprotective effects conferred by estrogens is thought to be complex and mutifactorial, and still remains obscure. It is well established that K+ channels broadly expressed in a variety of neural subtypes determine the essential physiological features of neuronal excitability, and dysfunction of these channels is closely associated with diverse brain deficits, such as ataxia and epilepsy. A growing body of evidence supports a neuroprotective role of K+ channels in malfunctions of nervous tissues, even taking as a therapeutic target in the clinical trials. As a multi-target steroid hormone, estrogens also regulate the activity of distinct K+ channels to generate varying biological actions, and accumulated data delineate that some aspects of estrogen-mediated neuroprotection may arise from its impact on multiple K+ channels, including Kv, BK, KATP and K2P channels. The response of these K+ channels after acute or chronic exposure to estrogens may oppose pathological abnormality in nervous cells, which serves to extend our understanding for these phenomena.